(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
• In the legal tradition that comes down to us from the 19th century, legal proceedings did not really have a legitimizing purpose, but more of an instrumental function (due process of law), aimed at protecting rights or making binding and correct decisions. The legitimacy of the right recognized and affirmed appeared as an external and subsequent result of the process. In the explanatory memorandum to the 1973 CPC, Alfredo Buzaid acknowledged that civil procedure was "an instrument that the State places at the disposal of litigants in order to administer justice". In this sense, he said, if the aspiration of each of the parties to the conflict was to be right, the purpose of the process was to give reason to those who were right. This meant, in fact, not a private interest, but the public interest of society as a whole. Thus, the process had to be geared towards ensuring compliance with the law, and had to be equipped exclusively with rational means, aimed at meeting two requirements: speed and justice. For all these reasons, the 1973 reform proposed a strictly technical plan, focusing on the jurisdictional function of knowledge, execution and precautionary measures. This conception assumed that the judicial process was strictly constituted to determine and ensure the application of the laws that guarantee the inviolability of individual rights. In carrying out this mission, judicial decisions are programmed and not programmatic, that is, they are decided on the basis of the law, the Constitution, general principles of law, customs, and are valid for the case for which the Judiciary was called upon, and cannot be extended to other cases. Today, with the advent of a technologically mass society (internet, social networks) and a technologically bureaucratic welfare state (computerized bureaucracy), demands seem to be developing for a political de-neutralization of the judge, who is then called upon to perform a socio-therapeutic function, freeing himself from the tight constraints of strict legality and the exclusively retrospective responsibility it imposes (judging facts, judging the past in the name of the given law), forcing himself into a prospective responsibility, concerned with achieving political ends (judging in order to provide for the future). And he is no longer exempt from this in the name of the principle of formal legality (dura lex sed lex). This transformation is not simply a matter of correcting the literalness of the law in the specific case by means of equity or the obligation, in the contentious application of the law, to look at the social purposes for which it is intended. This already existed. The judge’s responsibility now includes responsibility for the political success of the goals imposed on the other powers by the demands of the welfare state. In other words, like the Legislative and Executive branches, the Judiciary becomes responsible for the coherence of its attitudes in line with projects for social change, and it is postulated that any failures in its decisions should be corrected by the judicial process itself.